Reka Bentuk Menulis Makalah di Era Merdeka Belajar Melalui Kerangka Kemampuan Berpikir Kritis - Harsono,; Hafsi, Ainur Rofiq; Citra, Dela Kuniawati; Amalia, Laili; Roviva, (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this development research is to develop teaching materials for writing papers based on critical thinking skills. This research and development uses 3D models. Based on the results of a study by linguists and material experts, it shows that teaching materials for writing papers are categorized as feasible in terms of content eligibility, an average of 73%, presentation with an average of 74%, language use with an average of 72%, and graphics obtained with an average of 6.8%. Students who become data sources are able to think critically in writing papers with 70.33% analytical skills, 41.18% evaluation, 50.20% self-regulation, 63.19% interpretation, and 63.75% explanation. Teaching materials for writing papers based on critical thinking skills can be used as supporters in the Merdeka Belajar era.